(untitled) (Research, Society and Development, 2020)
Arsenic is considered a metalloid, widely distributed across the globe, found naturally in the environment. It is usually presented in the form of sulfide and in a huge variety of minerals, presenting very toxic characteristics, even in small quantities. Arsenic can also cause contamination of soils, waters and food and, consequently, possible intoxications to humans. Therefore, the present article aims to assess the risk to human health by ingesting water contaminated by arsenic (main focus) and also in food (through the use of water in cooking rice) in regions of Portugal. The approach of this study was quantitative, through a risk assessment methodology, through the elaboration of scenarios, in which they were used, based on a review of studies previously carried out, seeking to investigate the values ​​of arsenic concentrations in waters, as well as in food, in order to get to know each other better and have a perception of possible harm to human health caused by this metalloid. The main results showed that if the consumption of water for 3 years is 3 liters per day (per inhabitant), with an arsenic concentration that on average is equivalent to 0.800 mg / L of water, it can cause a highly potential danger to human health. Likewise, consumption of rice (70g) for 5 days a week for 50 years, causes the individual to consume the same 0.800 mg / L of arsenic. This union of ingestion can be highly harmful to health, leading to numerous diseases, including cancer.